"Damned if You Do, Damned if You Don't": Perceptions of Guns, Safety, and Legitimacy Among Detained Gun Offenders. (January 2016) - Barragan, Melissa; Sherman, Nicole; Reiter, Keramet; Tita, George E.
Procedural justice research generally indicates that legitimacy produces compliance when people perceive the law and legal actors to be fair. Drawing upon 140 in-depth interviews with gun offenders detained in Los Angeles County jails, this article examines legal and extra-legal factors that influence illegal gun possession. Although prior research studies on legal and illegal gun carrying have suggested a relationship between (a) safety perceptions and possession and (b) legal perceptions and possession, few have deeply interrogated how such perceptions develop and interact to inform ideas of legitimacy and compliance with gun laws. Our findings suggest that feelings of insecurity coupled with perceptions of, and experiences with, law enforcement interacted in complex ways to condition legitimacy-based beliefs, and ultimately, compliance. Although many of our respondents viewed the law as legitimate in the abstract, they believed it to be illegitimate in individual application, especially where rules and sanctions failed to account for personal experiences of insecurity.